2018
DOI: 10.1111/1346-8138.14536
|View full text |Cite
|
Sign up to set email alerts
|

Negative‐pressure closure was superior to tie‐over technique for stabilization of split‐thickness skin graft in large or muscle‐exposing defects: A retrospective study

Abstract: Skin grafts are frequently used for the reconstruction of skin defects, and optimal stabilization of the graft is essential for successful reconstruction. Although the tie-over technique has been widely used as a standard method in Japan, we sometimes encounter cases with significant graft loss due to suboptimal stabilization of the graft. Reported risk factors for increased graft loss include the following: defects of a large size, with muscle exposure, and located in the trunk and extremities. Recent studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…Additionally, they demonstrated that VAC could be used in locations that were anatomically challenging for the placement of conventional bolster dressings, such as the trunk, thighs, and other contoured areas [18]. The SFSG take rates of VAC and conventional bolster dressings were reported to be 96% and 89%, respectively by Scherer et al [19] and 97.9% and 79.2%, respectively by Nakamura et al [20]. In another study, VAC was reported to improve the SFSG rate by improving the revascularization process and preventing the accumulation of seroma or exudate (which can interfere with adhesion) beneath the graft [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, they demonstrated that VAC could be used in locations that were anatomically challenging for the placement of conventional bolster dressings, such as the trunk, thighs, and other contoured areas [18]. The SFSG take rates of VAC and conventional bolster dressings were reported to be 96% and 89%, respectively by Scherer et al [19] and 97.9% and 79.2%, respectively by Nakamura et al [20]. In another study, VAC was reported to improve the SFSG rate by improving the revascularization process and preventing the accumulation of seroma or exudate (which can interfere with adhesion) beneath the graft [8].…”
Section: Discussionmentioning
confidence: 99%
“…Shin et al retrospectively reviewed 10 FTSG cases from the anterolateral thigh (ALT) with the aid of a postoperative VAC, and reported that the thick skin of the FTSG possessed more tension than that of the STSG, resulting in uneven pressure on the wound bed and subgraft fluid accumulation; thus, the use of VAC is feasible for improving FTSG outcomes [21]. The decrease in operative time using VAC compared with the tie-over bolster technique was demonstrated in a study by Nakamura et al [20]. Nonetheless, the limitations of VAC include additional short-term medical costs and adhesion during dressing removal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Recently, we conduced retrospective study to compare NPC and the conventional tie-over method for skin graft stabilization using data of patients with defects in the trunk and extremities of >10 cm or with muscle exposure, because no such comparative studies had been reported. 3 In this study, NPC showed not only higher survival of the skin graft, but also shorter operative time, suggesting that NPC may be superior to tie-over methods for stabilization of skin graft. However, the usefulness of NPC for graft stabilization is yet to be fully established.…”
Section: Introductionmentioning
confidence: 51%